Faktor-Faktor yang Berhubungan dengan Kejadian TB Paru pada Anak di Poliklinik RSUD Embung Fatimah - Christy Heny Tripena; Fitriany Suangga; Indah Purnama Sari (Pusat Riset dan Inovasi Nasional, 2024)
Pulmonary TB in children is an infection caused by the germ Mycobacterium Tuberculosis. Pulmonary TB is transmitted from human to other human through the air when a BTA positive pulmonary TB sufferer talks, sneezes or coughs and indirectly the sufferer emits phlegm splashes in the air and there are ±3000 phlegm splashes containing germs. This research was conducted to determine the factors associated with the incidence of pulmonary TB in children at the Embung Fatimah Regional Hospital Polyclinic. The research method is descriptive with a cross sectional design. The sample consisted of 34 pediatric TB patients at the Embung Fatimah Regional Hospital Polyclinic using a sampling technique, namely total sampling. Data were processed using the chi square test. The results of this study show that there is no significant relationship between BCG immunization status and the incidence of pulmonary TB in children (P value of 0.450 > 0.05), there is a significant relationship between contact with TB sufferers and the incidence of TB in children (P value of 0.021 > 0.05), and there is a significant relationship between family smoking status and TB sufferers and the incidence of TB in children (P value of 0.014 > 0.05). It is hoped that the role of nurses can overcome the problem of childhood TB through health promotion and increasing immunization coverage for children in the community.